(3JMaI GdfGXQ aj MaX GdTYGFQs - (3eMeO Hf eMeO GdJLjj, CHh YHO Gddg GdYbHGfj,J (B680 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi ef GQJcH eNCdag fgjg hCeQg s
(3BNQgG (B:s
(3Cf jhbY Edi GdeMJSH hde jLR ddeMJSH Cf jhbY Edi hGMO efgeG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B261s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs